Adjusting to the unexpected: A review of the Journal of Management History from 2000 to 2004. Issue 4 (14th September 2015) - Jain, Ajay K.; Sullivan, Sherry
Abstract : Purpose: – This study aims to provide a literature review of the 56 articles published in the Journal of Management History (JMH) from 2000 to 2004. Design/methodology/approach: – The authors conducted a thematic analysis using the categories of person, topic or event to classify articles as well as a citation analysis using Google Scholar. Findings: – The number of articles published from 2000 to 2004 was almost 50 per cent fewer than published in the previous five years, and citation rates were lower. Originality/value: – Results suggest that high-quality articles focused on persons or topics are more likely to be published in the JMH.